Acquired factor V inhibitor in the setting of coronavirus disease 2019 infection. Issue 4 (June 2021) - Bennett, Joseph; Cunningham, Mark T.; Howard, Christin; Hoffmann, Marc; Plapp, Fred V.
Abstract : N/A: Factor V inhibitors are a rare cause of life-threatening bleeding. We present a case of an acquired factor V inhibitor likely caused by coronavirus disease 2019 infection. Bleeding was manifested by severe anemia requiring frequent red-cell transfusion, left psoas muscle hematoma, and left retroperitoneal cavity hematoma. Factor V activity was less than 1% and the factor V inhibitor titer was 31.6 Bethesda units. Severe acute respiratory syndrome coronavirus 2 RNA testing of the nasopharynx was positive 2 weeks before presentation and continued to be positive for 30 days. The patient failed treatment with intravenous immunoglobulin and dexamethasone. Three cycles of plasmapheresis with fresh frozen plasma replacement resulted in correction of the bleeding and laboratory coagulopathy. This is the first reported case of a factor V inhibitor in a coronavirus disease 2019 patient and suggests that plasmapheresis may be a successful treatment strategy.